(untitled) (KULT_online, 2010)
In 2004 Richard Grusin coined the term ’premediation’ in order to highlight that the overall media concern of post 9/11 America lies in remediating the future, i.e. in making sure that the future as such has already undergone profound remediation (see: “Premediation.” In: Criticism, 46, 1, 17–39, 21). In his 2010 monograph on Premediation – Affect and Mediality after 9/11, Grusin provides a concise theory of premediation as a strategy of securitisation that has made outdated the former media regime of surveillance (see p. 126). Building on recent findings in affect theory, embodied realism, and (media) philosophy, Grusin shows how media formations govern the distribution of affect and, consequently, human action and sentiment, and thus function as powerful political players.